2006
DOI: 10.1590/s0074-02762006000500007
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium berghei ANKA infection induces thymocyte apoptosis and thymocyte depletion in CBA mice

Abstract: Immune responses to malaria infections are characterized by strong T and B cell activation, which, in Key words: malaria -thymus -Plasmodium berghei -mice Malaria infections are characterized by defective immune responses, with poor efficacy and, in some cases, with the occurrence of immunopathology. The major lifethreatening malaria-related complications -cerebral malaria and severe anemia -have a strong immunological component in humans (Mackintosh et al. 2004) as well as in experimental models (De Souza &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 17 publications
2
12
0
Order By: Relevance
“…2003). Here we provide detailed description of the changes in these organs that were similar to changes observed in PbA‐inbred mouse models (Rest 1982; Carvalho et al. 2000, 2006, 2007).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…2003). Here we provide detailed description of the changes in these organs that were similar to changes observed in PbA‐inbred mouse models (Rest 1982; Carvalho et al. 2000, 2006, 2007).…”
Section: Discussionmentioning
confidence: 74%
“…2000) and on lymphoid organs, which act both as targets and as players in CM pathogenesis (Urban et al. 2005; Carvalho et al. 2006, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This can result in apoptosis in monocytes, B cells, T cells, and DCs (194–199). Acute infection can also lead to thymus apoptosis and depletion, thereby diminishing the output of new naïve T cells (200). On the other hand, chronically activated T cells (both αβ and γδ) during lingering blood infection or multiple reinfections can also enter a phase of anergy (201203) and/or exhaustion (204).…”
Section: Immunosuppressionmentioning
confidence: 99%
“…Although immune responses to malaria and physiopathogenesis of cerebral malaria in mice have been widely studied [14-17], detailed analysis of changes in lymphoid compartments, which is basic to understand how the immune system respond to a challenge, has not been widely approached, with a few works mainly on the Plasmodium chabaudi model [18-20]. It has recently been shown that P. berghei ANKA-infected CBA mice develop various degrees of thymocyte apoptosis, leading in some cases to thymocyte depletion and severe thymus cortical atrophy [21]. In the present work, attention was focused on the sequential immunohistopathological changes caused by P. berghei ANKA infection in several lymphoid compartments and their possible implications in pathology and immunity of the infection.…”
Section: Introductionmentioning
confidence: 99%